Status of biodiesel research and development in Pakistan - Chakrabarti, M.H.; Ali, M.; Usmani, J.N.; Khan, N.A.; Hasan, D.B.; Islam, M.S.; Abdul Raman, Abdul Aziz; Yusoff, Rozita; Irfan, M.F. (Elsevier, 2012)
Performance of biodiesel in engines is well established and biodiesel is currently adjudged as a low carbon fuel with the most potential of replacing fossil fuels. The fossil fuel sources are dwindling in Pakistan resulting in importation of about 8.1 million tonnes at approximately US 9.4 billion per annum. In the ambit of this justification, augmenting the energy scarce resources in Pakistan through intense harnessing of the varied biodiesel sources can adequately address the deficiency and can ensure energy security. Towards this end, the progress attained in biodiesel related researches in Pakistan are evaluated and presented with the view of highlighting ways of achieving the target set by the Government. A feedstock that drew less attention is spent triglycerides, and the little work reported by some organizations appeared promising. Now the onus is upon organizations such as the Alternative Energy Development Board and Pakistan State Oil to harness the research results from several indigenous Universities and develop a full-scale biodiesel economy in Pakistan.